Investigation of Al2O3 nanoparticle influence on caloric properties of isopropanol - Shimchuk, N.A.; Zhelezny, V.P. (Хабаршы. Физика сериясы, 2015)
The aim of this work is the experimental studying the caloric properties of the model nanosystems – isopropyl alcohol with nanoparticles of alumina oxide (Al2O3) at different nanoparticle concentrations. Study of thermophysical properties of these model systems is required to assess the of nanoparticle’s influence on the phase equilibria parameters and heat caloric properties of working fluids and coolants with nanoparticle additives promising for use in refrigeration systems.